If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -5)(3x + 4) = 0 Reorder the terms: (-5 + 2x)(3x + 4) = 0 Reorder the terms: (-5 + 2x)(4 + 3x) = 0 Multiply (-5 + 2x) * (4 + 3x) (-5(4 + 3x) + 2x * (4 + 3x)) = 0 ((4 * -5 + 3x * -5) + 2x * (4 + 3x)) = 0 ((-20 + -15x) + 2x * (4 + 3x)) = 0 (-20 + -15x + (4 * 2x + 3x * 2x)) = 0 (-20 + -15x + (8x + 6x2)) = 0 Combine like terms: -15x + 8x = -7x (-20 + -7x + 6x2) = 0 Solving -20 + -7x + 6x2 = 0 Solving for variable 'x'. Factor a trinomial. (-4 + -3x)(5 + -2x) = 0Subproblem 1
Set the factor '(-4 + -3x)' equal to zero and attempt to solve: Simplifying -4 + -3x = 0 Solving -4 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -3x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -3x = 0 + 4 -3x = 0 + 4 Combine like terms: 0 + 4 = 4 -3x = 4 Divide each side by '-3'. x = -1.333333333 Simplifying x = -1.333333333Subproblem 2
Set the factor '(5 + -2x)' equal to zero and attempt to solve: Simplifying 5 + -2x = 0 Solving 5 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 0 + -5 -2x = 0 + -5 Combine like terms: 0 + -5 = -5 -2x = -5 Divide each side by '-2'. x = 2.5 Simplifying x = 2.5Solution
x = {-1.333333333, 2.5}
| 5x(63-16)= | | m^3-6=0 | | (4w-8)(w+3)=0 | | -2in(x)+in(y)=in(6) | | 6x^2-11x-13=5(x^2-1)+3 | | 8+6x=7x-5 | | V+4=-5 | | Y=-16x+20x+5 | | 3X^(7/3)-6=0 | | 5x^3=85 | | (4y-8)(3y+7)=0 | | w=mxf+eforx | | z(z+7)=0 | | 12x6/6x3 | | -4q-(-7.3)=45.9 | | 1x+.12x=34000 | | (X6)6/x3 | | 12x-8=14x-34 | | -3.6+2z=13.6 | | -3x+5y=34whenx+3y-18 | | 8(p+1)-8= | | 31.9=-7+4m | | -3x+5y=34 | | -12+k=7.15 | | 2x+145=9x-9 | | y=x^3/x^2-1 | | 50x+60x=50x+80x | | -5=t/19-2 | | (6y^2-7y-5)(y-8)= | | 2x+15=-35 | | 4x-2(3x-1)=18 | | 5n+2=n+7 |